Kajian Persepsi Masyarakat Terhadap Pengelolaan Sumber Daya Air Di Desa X - Daeli, Serta Denius (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the community’s perception of water resource management in Desa X. The research employed a descriptive quantitative approach, with data collected through questionnaires, interviews, observations, and documentation. The population consisted of all household heads in Desa X, and the sample size was determined using Slovin’s formula with a 5% margin of error and a proportional random sampling technique. Data analysis was conducted descriptively to determine the average perception scores based on four indicators: water availability, water quality, management, and community participation.The results showed that the overall community perception was categorized as good, with an average score of 3.98. The highest scores were obtained for water availability (4.15) and water quality (4.05), while the management indicator (3.78) had the lowest score, indicating a need for improvement. Community participation (3.92) was generally good, although some residents were less active. These findings suggest that water resource management in Desa X is relatively good but requires enhancements in governance, transparency, and community empowerment to achieve more sustainable management.